ABREVIATION OF PREOPERATIVE FASTING TIME: LITERATURE REVIEW - Fernandes Guimaraes, Rodrigo; Klênio Confessor de Sousa, Raphael; Andrino da Silva, Wallace (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2023)
Introduction: The practice of preoperative fasting has been established since the last century and, since then, the traditional concept of fasting and water deprivation has been questioned by anesthetists and surgeons after years of practice. Several protocols have been proposed by societies, but this reality, however, is not consistent with the practice carried out in many health care centers. Objective: Conduct a literature review and analyze the studies that shortened the preoperative fasting time published in the last 5 years. Method: The selection of papers was carried out in February 2023 in the PUBMED database. It was used as descriptors: fasting AND preoperative AND shorten. The time frame was the last 5 years. Results: The search ended with 12 articles that adequately met the inclusion criteria. Conclusion: The abbreviation of the preoperative fasting time of 2 hours for clear liquids may be possible, safe, and promotes benefits. For the patient, it is able to improve comfort, reduce thirst and hunger, improve gastrointestinal function and decrease preoperative anxiety. In addition, it reduces the use of analgesics, the volume of intravenous infusion and stabilizes blood glucose, insulin and electrolyte levels.